Correlative Microscopy: Site‐Specific SERS Assay for Survivin Protein Dimer: From Ensemble Experiments to Correlative Single‐Particle Imaging (Small 32/2017). Issue 32 (August 2017) - Wissler, Jörg; Bäcker, Sandra; Feis, Alessandro; Knauer, Shirley K.; Schlücker, Sebastian
Abstract : An assay for protein dimers using surface‐enhanced Raman scattering (SERS) is presented, in article number1700802, by Sebastian Schlücker and co‐workers. Site‐specific binding of the Survivin protein dimer to molecularly functionalized gold nanoparticles results in the formation of protein‐bridged dimers of gold nanoparticles. The dimers exhibit the characteristic SERS spectrum of Raman reporter molecules in the hot spot generated upon resonant laser excitation.